The Nemesia trapdoor spider fauna of the Maltese archipelago, with the description of two new species (Araneae, Mygalomorphae, Nemesiidae) - Cassar, Thomas; Mifsud, David; Decae, Arthur E. (European Journal of Taxonomy, 2022)
Contrary to what its name suggests, Nemesia arboricola is not strictly arboreal in habit. Here we compare female specimens of N. arboricola collected from arboreal and terrestrial nests. We furthermore describe the male of N. arboricola for the first time as well as two recently discovered species of Nemesia (N. maltensis sp. nov. and N. cominensis sp. nov.). Nemesia maltensis is described from both sexes, N. cominensis is described from the female and a juvenile male specimen. For N. cominensis we discuss the sexual dimorphism of juvenile male and female spiders. Field observations and laboratory observations show remarkable features of the Maltese Nemesia fauna that are unknown from Nemesia species found elsewhere. Particularly, the arboreal dwellings of N. arboricola and the absence of a trapdoor to close off the burrow entrance in N. maltensis appear to be exceptional. The composition of the Maltese Nemesia fauna, as located in the central Mediterranean, is finally discussed in relation to the different Nemesia species-complexes occurring in the eastern and western Mediterranean basin.